EVALUATION OF BIOGAS CALORIFIC POTENTIAL FOR USE IN MEDICINAL PLANT DRYERS - Corrêia, Arlindo Fabricio; Godoy, Antonio Cesar; Feiden, Armim; Siqueira, Jair Antonio Cruz; Soares, Caroline Tietz (ENERGIA NA AGRICULTURA, 2016)
The objective of this study was to evaluate the use of thermal energy from the burning of biogas for heating air and its potential use in a drying chamber. A prototype was built to evaluate the air heating in the heating system and in a drying chamber. The biogas composition used was 60.00% methane (CH4). Treatments were composed by pressure difference applied to biogas, in which: T0 (no heating), T1 (pressure 130.00 to 200.00 kPa), T2 (pressure 200.00 to 270.00 kPar) and T3 (pressure 270.00 to 340.00 kPar) in six replications. A gas water heater (LPG) was adapted for use with biogas. The drying chamber was built with MDF (Medium Density Fiberboard) boards and thermally insulated with a total usable volume of 0.544 m³ and air velocity of 1.58 m.s-1. The burning of biogas generated 36,10MJ h-1, 68.95MJ h-1 and 76.03MJ h-1 for treatments T1, T2 and T3 respectively, meeting the need for heating in the drying chamber operating at temperatures of 43.05 ºC (T1), 52.56 ºC (T2) and 53.56 ºC (T3). The heating system proposed has proved to be effective for drying different species of medicinal plants, since it meets the temperature range specified in the literature.